Rapid genetic and morphologic divergence between captive and wild populations of the endangered Leon Springs pupfish, Cyprinodon bovinus. Issue 8 (18th February 2017) - Black, Andrew N.; Seears, Heidi A.; Hollenbeck, Christopher M.; Samollow, Paul B.
Abstract: The Leon Springs pupfish ( Cyprinodon bovinus ) is an endangered species currently restricted to a single desert spring and a separate captive habitat in southwestern North America. Following establishment of the captive population from wild stock in 1976, the wild population has undergone natural population size fluctuations, intentional culling to purge genetic contamination from an invasive congener ( Cyprinodon variegatus ) and augmentation/replacement of wild fish from the captive stock. A severe population decline following the most recent introduction of captive fish prompted us to examine whether the captive and wild populations have differentiated during the short time they have been isolated from one another. If so, the development of divergent genetic and/or morphologic traits between populations could contribute to a diminished ability of fish from one location to thrive in the other. Examination of genomewide single nucleotide polymorphisms and morphologic variation revealed no evidence of residual C. variegatus characteristics in contemporary C. bovinus samples. However, significant genetic and morphologic differentiation was detected between the wild and captive populations, some of which might reflect local adaptation. Our results indicate that genetic and physical characteristics can diverge rapidly between isolated subdivisions of managed populations, potentially compromising the value of captive stock for future supplementation efforts. In the case of C. bovinus, our findings underscore the need to periodically inoculate the captive population with wild genetic material to help mitigate genetic, and potentially morphologic, divergence between them and also highlight the utility of parallel morphologic and genomic evaluation to inform conservation management planning.